Thirty Years of the Večernica Award: Award-winning and nominated works for the Večernica Award 1997–2026 - Haramija, Dragica (Trideset let literarne nagrade večernica, 2026)
The Večernica Award is a literary award in Slovenia for original children’s and young adult (YA) literature, bestowed since 1997 in Murska Sobota as part of Oko Besede (Eye of the Word), a literary festival for writers of this genre. The article presents the Oko Besede Festival, the initiative for creating the Večernica Award, the basic rules regarding the jury and the method of selecting nominated and awarded literary works. The main part of the article is devoted to award-winning and/or nominated works, especially authors who have been nominated for or won the Award multiple times, as well as the literary genres and types most often represented in the selection of nominated/award-winning literary works. Also presented is the evolution of the Večernica Award and its role in the development of original Slovene children’s and YA literature.